The Relationship between Knowledge and Emergency Response Attitude to the Mount Agung Eruption Disaster - Ni Kadek Ayu Purnama Dewi; Ni Made Dewi Wahyunadi; IGA Tresna Wicaksana; Ni Luh Putu Inca Buntari (GLOBAL HEALTH SCIENCE GROUP, 2026)
Disaster emergency response is a rapid action to mitigate the impact of a disaster. Therefore, community emergency response is crucial in reducing risk. This requires knowledge and training to enable the community to act appropriately and effectively when a disaster occurs. To determine the relationship between community knowledge and emergency response attitudes regarding the Mount Agung eruption in Tunas Sari Hamlet, Karangasem Regency. This study used a quantitative, correlative analytical approach with a cross-sectional approach, with a sample of 350 respondents selected using a purposive sampling technique. Data collection used a knowledge questionnaire and an attitude questionnaire. The questionnaire for the variables of the level of knowledge and attitudes of the community towards evacuation routes was compiled by researchers based on relevant theories and indicators, then a content validity test (face validity) was carried out through expert judgment by two expert lecturers. Data analysis was descriptive. The Kolmogorov-Smirnov normality test indicated that the data were not normally distributed, therefore the Spearman's Rho test was used. The majority of respondents had good knowledge (67.1%) and moderate emergency response attitudes (64.6%). The Spearman's Rho test showed a significant relationship between knowledge and emergency response attitudes (p<0.001) with a correlation coefficient of r=0.326, indicating a positive relationship with weak strength. Increased disaster education, training, and routine simulations are recommended to strengthen the community's emergency response skills.